"Nanofabrication Towards Biomedical Applications: Techniques, Tools, Applications, & Impact" - Kumar (C S S R) Ed.; Hormes (J) Ed.; Leuschner (C) (2005)
Nanofabrication ; Biomedical
22.5
Keywords: Nanofabrication ; Biomedical